Heart Care Augmented Reality Mobile Simulation (heARt) - Mohamed, F. (Institute of Electrical and Electronics Engineers Inc., 2016)
Heart Care Augmented Reality Mobile Simulation (heARt) is an edutainment mobile based application that will helps in gaining such awareness of maintaining a healthy heart among the society. This application are augmented reality application that will combined both reality world and virtual reality world in order to give the users an interactive content of information. This application are developed to replace a traditional pamphlets or brochures that have no interactive content within it. HeARt, allows users to interact with the information that presented virtually on their phone screen. This kind of features are believed to be a lot more interesting in contrast with traditional brochures and pamphlets.